MICROETHICS IN ACTION1 - Nikku, Nina (Bioethics, 2006)
The future development of bioethics has been discussed in a number of articles in recent years, principally with regard to the trend towards empirical studies. However, what is meant by empirical studies in this context and how it is to be used concretely have been subject to varying interpretations. The purpose of this article is to develop what we term the microethical approach as a concrete method for an empirically driven bioethics. By adopting a microethical perspective, we will illustrate an analytical concept for describing and demonstrating how, as a result of contextual circumstances and forms of understanding, different individuals in their everyday life adopt different coping strategies and behavior patterns in relation to ethical values. From a deepened perspective, the complexity of human behavior becomes apparent, and knowledge is gained about how moral problems are perceived and construed by those whom they in fact affect. We intend first and foremost to develop the microethical methodology by elucidating the methods and approaches that can help in clarifying moral dilemmas on a microethical level, and how the relationship between the empirical material and the ethical analysis evolves over the course of the analysis. This is exemplified by a study of caregivers’ entrance into patients’ private lives through the provision of care and assistance in the home.